NMR study of aqueous tetraalkylammonium silicates - Syvitski, Raymond Thomas (My University, 1994)
Silicon-29 nuclear magnetic resonance (NMR) spectroscopy has been used to investigate the equilibrium distribution and kinetics of silicate oligomers in aqueous tetraalkylammonium silicate solutions. Certain tetraalkylammonium cations (particularly tetramethylammonium cation) stabilize specific silicate oligomers, such as the cubic octamer and prismatic hexamer, by forming a protective shell that shields these oligomers from interaction with paramagnetic ions and impedes Si-Si chemical exchange. For tetramethylammonium silicate solutions, the dependence of the initial rate of cubic octamer formation on alkalinity, silica concentration and tetramethylammonium cation concentration has been investigated and a mechanism for the formation of cubic octamer proposed. For tetraalkylammonium silicate solutions with OH~:Si < 1:1 which favour the cubic octamer, at least four resonances which occur down-frequency of the cubic octamer resonance have been attributed to stable protonated states of the cubic octamer. Alkali-metal cations added to tetramethylammonium silicate solutions destabilize the cubic octamer probably by displacing tetramethylammonium cations which surround the oligomer.
Keywords: Silicates analysis; Nuclear magnetic resonance spectroscopy; Aqueous silicate chemistry; Zeolite synthesis